ANALISIS DAMPAK PROGRAM ASURANSI KESEHATAN TERHADAP PEMBIAYAAN RUMAH SAKIT DI INDONESIA - Aprilia Putri Batubara; Kayla Devina, Nadiah Wulandari, Fitriani Pramita Gurning (CV. Adiba Aisha Amira, 2024)
A person's health is very important in life. In addition, good health is supported by adequate and superior facilities. In addition, the insurance industry needs to provide services that provide protection for humans, especially those related to activities that are beneficial to public health. The aim of this research is to determine the relationship between the quality of health services and health insurance in Indonesia. The method used is to analyze articles published in the last 5 years through Google Scholar, Sinta, and Garuda searches. The results of this research are that the resources and mentality of implementers become the driving force for public policies made by the government. According to journals collected, more than 50% of the public feel that direct execution of public policy is the biggest motivator, both in implementing health service policies and other policies. They also note community initiatives and involvement. The quality of health services received is in accordance with the health insurance paid by the community. With health insurance, it is very useful in health services, patients are seen as the parties who utilize and benefit from these services, and they are also the parties who have the greatest influence on the quality of services provided.